2018
DOI: 10.1186/s12958-018-0410-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of levothyroxine supplementation on pregnancy outcomes in women with subclinical hypothyroidism and thyroid autoimmuneity undergoing in vitro fertilization/intracytoplasmic sperm injection: an updated meta-analysis of randomized controlled trials

Abstract: BackgroundEvidence suggests that subclinical hypothyroidism (SCH) and thyroid autoimmunity (TAI) are associated with adverse pregnancy outcomes. This systematic review and meta-analysis was conducted to determine whether levothyroxine (LT4) supplementation would improve pregnancy outcomes among infertile women with SCH and/or TAI who underwent in vitro fertilization (IVF) or intracytoplastic sperm injection (ICSI).MethodsWe searched databases of PubMed, EMBASE, Web of Science, Cochrane Controlled Trials Regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 32 publications
1
32
0
1
Order By: Relevance
“…But they paid no attention to treatment. Several meta‐analyses of studies of ART patients with higher levels of TPO‐Ab showed that substitution of thyroid hormones decreased the rate of miscarriages, 10,58,59 and increased the delivery, clinical pregnancy, and fertilization rates 60 . However, other studies such as the study by Wang published in 2017 27 were unable to demonstrate the effect.…”
Section: Discussionmentioning
confidence: 99%
“…But they paid no attention to treatment. Several meta‐analyses of studies of ART patients with higher levels of TPO‐Ab showed that substitution of thyroid hormones decreased the rate of miscarriages, 10,58,59 and increased the delivery, clinical pregnancy, and fertilization rates 60 . However, other studies such as the study by Wang published in 2017 27 were unable to demonstrate the effect.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, the authors excluded the populations most likely to benefit, and therefore their findings are only potentially applicable to women at low risk of miscarriage. Nevertheless, this study was included in a recent meta-analysis, along with three prior much smaller RCTs studying the impact of levothyroxine on obstetrical outcomes in euthyroid patients with subclinical hypothyroidism or thyroid autoimmunity undergoing IVF (20). With the inclusion of this study, the meta-analysis concluded that levothyroxine treatment has no statistically significant impact on live births in women with subclinical hypothyroidism or thyroid autoimmunity undergoing IVF; however, it does decrease miscarriage rates by *50% (20).…”
Section: Thyroid Autoimmunitymentioning
confidence: 99%
“…Самый последний систематический обзор, посвященный данной проблеме, проведен Rao et al в 2018 г. [43] на основании вышеперечисленных статей [38][39][40]42]. Путем метаанализа исходов циклов ВрТ у 787 бесплодных пар не был установлен положительный эффект тироксина на такие показатели, как частота наступления клинической беременности (Ор 1,46; 95 % ДИ 0,86-2,48; р = 0,16), частота живорождения на цикл ЭКО/ИКСИ (Ор 2,05; 95 % ДИ 0,96-4,36; р = 0,06), преждевременные роды до 37 нед.…”
Section: влияние заместительной терапии L-тироксином на исходы програunclassified